Update on weight-gain caused by antipsychotics: a systematic review and meta-analysis. Issue 3 (3rd March 2020) - Barton, Barbara B; Segger, Felix; Fischer, Kai; Obermeier, Michael; Musil, Richard
ABSTRACT: Introduction : Antipsychotic-induced weight-gain (AIWG) is a very important, yet often neglected side-effect in the treatment with first and second generation antipsychotics. AIWG can increase the risk of developing metabolic syndrome, diabetes and cardiovascular disease. Meta-analyzes mostly concentrate on AIWG in schizophrenic and bipolar patients, even though antipsychotics are prescribed off-label across many other diagnostic groups (e.g. anxiety disorders, depression, autistic disorder). Areas covered : Pub Med and Web of Science were systematically searched for RCTs reporting on AIWG with a sample size of ≥ 100 published between 2014 and 2019. All diagnoses and ages were included. Expert opinion : Inclusion criteria were fulfilled by 27 RCTs. All antipsychotics led to significantly more weight-gain (p < .001) and most antipsychotics led to a significantly higher risk for a clinically relevant weight-gain of ≥7% compared to placebo (RR = 2.04). The results support previous findings that weight-gain occurs quickly. To efficaciously and efficiently tackle the problem of AIWG in clinical practice and trials, people at high risk need to be identified by predictive tools enabling the clinician to offer tailored adjunctive therapies (medication and/or lifestyle interventions). Most importantly, weight and metabolic monitoring ought to be consequently implemented in clinical routine in the treatment of any patient with any diagnosis when antipsychotics are prescribed.